Stomatological management of patients with liver disease: A review of the literature - Cancino, Javiera (2023)
Introduction: The liver is the organ responsible for the metabolism of nutrients, some drugs, and the production of coagulation factors. According to the World Health Organization, approximately 23 million people worldwide are diagnosed with liver disease each year. As a result, it is common for dentists to encounter these patients on a daily basis in their practice. The objective of this review is to establish the dental management of patients with liver disease. Material and methods: A manual literature search was conducted using the indexed articles in PUBMED and EBSCO databases using the keywords “oral surgery,” AND “liver disease,” AND “hepatic cirrhosis,” AND “dental management”. Results: Patients with liver disease present important characteristics for the dentist, which must be recognized in order to perform procedures with the lowest risk of intraoperative and postoperative complications. A patient with poorly controlled underlying liver disease is more prone to infections and bleeding, which implies a high risk of morbidity. Conclusions: Dental care for patients with liver disease should be assessed according to the reason for consultation, control of the disease, the complexity of the procedure to be performed, and both intraoperative and postoperative hemostatic measures. All necessary hemostatic measures should be considered and dose adjustments should be considered in the use of NSAIDs.